Tissue Fractionation by Hydrostatic Pressure Cycling Technology: The Unified Sample Preparation Technique for Systems Biology Studies - Gross, Vera (The Association of Biomolecular Resource Facilities, 2008)
Major bottlenecks in systems biology studies arise from limitations of current sample preparation techniques. Multiple mutually exclusive sample preparation methods, which are often required to extract distinct classes of molecules from cells and tissues, are incompatible with studies of precious or very limited samples. Moreover, the strong detergents and chaotropic agents commonly required to solubilize sample constituents often interfere with subsequent separation and analysis. Here we describe a rapid, detergent-free sample preparation technique that allows efficient concurrent isolation and fractionation of protein, DNA, RNA, and lipids from biological samples, eliminating the need for multiple replicates. The method relies on a synergistic combination of physical disruption of the cellular material by hydrostatic pressure (pressure cycling technology) and novel extraction conditions to dissolve and partition distinct classes of molecules into separate fractions. We demonstrate parallel recovery of proteins, lipids, and intact DNA and RNA, from animal cells and tissues, for proteomic, lipidomic, and genomic analyses. The protein extracts require minimal cleanup and are compatible with 1D and 2D PAGE, liquid chromatography coupled with tandem mass spectrometry, and Western blotting. The lipid fractions have been profiled by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry without further processing. The isolated DNA and RNA were shown to be intact by agarose gel visualization, and the presence of intact mRNA was confirmed by real time reverse transcription polymerase chain reaction. Analysis and comparison of samples extracted using this method and a more traditional extraction technique revealed several protein species preferentially extracted by the new method.